Development and evaluation of cannabidiol formulations for delivery to the central nervous system to treat neuropathic pain - Muresan, Paula Diana (2022)
Neuropathic pain is a great societal burden estimated to affect approx. 40% of the general population, being accompanied by a significant decline in normal functioning and quality of life. Moreover, it is a major economic burden, costing the NHS £5 billion annually. Pain has complex pathophysiology and is currently poorly managed due to the ineffectiveness of many therapies. The drawback associated with the development of novel analgesics is multifaceted. One of the limitations is linked to the lack of effective delivery of therapeutics to the site of action - the central nervous system (CNS). Effective drug delivery to the CNS is extremely challenging due to the presence of the blood-brain barrier (BBB) and the blood-cerebrospinal fluid-barrier (BCSFB), however a technique involving a direct intrathecal (IT) injection into the lumbar segment of the spinal cord by-passes these barriers. Additionally, numerous patients are also resistant to traditional opioids (i.e., morphine) used in the treatment of pain, leaving many with no alternative therapies. Nonetheless, cannabidiol (CBD) has been emerging as efficacious in treating pain, amongst other disease states such as depression, anxiety or inflammation. Therefore, in order to tackle neuropathic pain in patients resistant to traditional opioid therapies and by-pass the protective CNS barriers, the development of novel formulations coupled with effective interventional treatments is required.